2007
DOI: 10.1002/pssb.200572721
|View full text |Cite
|
Sign up to set email alerts
|

Poisson's ratio of simple planar ‘isotropic’ solids in two dimensions

Abstract: The influence of molecular geometry on the Poisson's ratio has been investigated for a few twodimensional (2D) hard body systems (hard discs, hard dimers, hard cyclic trimers, and hard cyclic hexamers) forming elastically isotropic solid phases. The Poisson's ratio of the studied periodic and aperiodic solids was determined by Monte Carlo simulations using the analysis of the box fluctuations in the constant pressure ensemble (NpT ) with variable box shape. The results obtained for all the studied systems show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…During last decade, there has been an increasing interest in the discovery and investigation of different physical systems [2][3][4][5][6][7][8][9][10][11][12] and/or models [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] which exhibit auxetic behavior (negative Poisson's ratio). This interest is motivated by at least two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During last decade, there has been an increasing interest in the discovery and investigation of different physical systems [2][3][4][5][6][7][8][9][10][11][12] and/or models [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] which exhibit auxetic behavior (negative Poisson's ratio). This interest is motivated by at least two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we devote our attention to the effects of molecule geometry and crystallographic structure. It has been shown that the geometry and specifically the anisotropy of a molecule can be of critical importance to the elasticity of the system [37,26,36]. Various kinds of disorder such as point and structural defects [38,39], voids [40], size polidyspersity of particles [41][42][43][44], and orientational disorder [37] also change the elastic properties of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the discovery of numerous auxetic materials [1,2,, ranging from synthetic polymeric foams [10][11][12][13][14][15][16] to naturally occurring silicates and zeolites [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Additionally, a number of auxetic models and structures have also been identified [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The other classes are namely chiral structures [7][8][9], rotating rigid/semi-rigid units [10][11][12][13][14], angle-ply laminates [15,16], hard molecules [17][18][19][20], micro porous polymers [21][22][23], and liquid crystalline polymer [24 -26]. In particular, the important 2D re-entrant structures are structurally hexagonal honeycomb, double arrow head structures, structures formed from lozenge grids, structure formed from sinusoidal ligaments, and structure formed from square grids [27].…”
Section: Introductionmentioning
confidence: 99%